Application of Mosaic Technique to Develop Children's Fine Motor Skills in PAUD Nurul Iman - Mirian Susanti; Manto Manto (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
From birth to six years of age, children participate in Early Childhood Education (ECE), a pre-basic education program that aims to prepare them for future learning through formal, non-formal, and informal means by providing them with educational stimuli that support their physical and spiritual development. Along with physical growth, children undergo a period of increased self-awareness, social competence, and environmental understanding throughout the early years of life. Researchers at PAUD Nurul Iman Desa Talang Baru want to learn more about the effects of mosaic techniques on the development of fine motor skills in young children so they can plan an appropriate study. The term